Growers’ Assessment on the Impact of Bactericides on Florida Citrus Groves - Singerman, Ariel (EDIS, 2018)
We conducted a survey among citrus growers to obtain their assessment on the impact of bactericides on yield one year after starting their use as a mitigating strategy against HLB. Forty-nine percent of the growers in our sample reported yield in their groves did not increase as a result of using bactericides. Thirty percent of the growers stated an increase in yield but only five percent had an adequate control to compare the results to. Eighty-seven percent of the growers stated they were planning on continuing bactericides use in 2017/18, suggesting they are expecting bactericides to have a positive effect over time. However, bactericides use and the pattern of substitutions growers made to accommodate its introduction into their budget seems to have contributed to psyllids’ insecticide resistance and, therefore, an increase in their population in Florida.